PERCEPTION SOCIETY ABOUT ENLARGEMENT ROADWAY PADANG ARO â LUBUK GADANG DISTRICT SANGIR SUB-PROVINCE SOUTH SOLOK. - Fitri, Deti Yuni; Rianto, Slamet; U, Iswandi (Pendidikan Geografi, 2013)
ABSTRACTThis research aim to to know Perception Society About EnlargementÂ  Roadway Padang Aro â Lubuk GadangÂ  District Â Sangir Sub-Province South Solok. Variable to research is: a) Indemnify, b) Perception Â society before enlargement of road, c) Perception of society after enlargement of road. this Research type is descriptive.Â Â Â Â Â Â Â Â Â Â Â  Population in this research is hit by family head EnlargementÂ  Roadway Aro â Lubuk GadangÂ  District Â Sangir Sub-Province South Solok. Sampel Research taken by sampling proposional. Responder Sampel taken with technique of proporsional sampling random with proportion 20%, sampel amount to 63 people. Technique analyse data use analysis with percentage formula. Technique data collecting Â or enquette of instrument.Result of research found that 1) Society express indemnation which is deliberation less according to, and less agree in indemnation given by government to enlargement of roadway Padang Aro â Lubuk Gadang. 2). Perception of society before enlargement of Â roadway Padang Aro â Lubuk GadangÂ  DistrictÂ  Sangir Sub-Province South Â Solok express price sell ground before enlargement of costly road, situation walke before enlargement of road often stuck, transportation fluency before enlargement of road less fluent, and living before enlargement of road remain to (there no change), 3). Perception of society after enlargement roadway PadangÂ  Aro â Lubuk GadangÂ Â  DistrictÂ  Sangir Sub-Province South Solok express enlargement of road influence price sell ground, earnings after enlargement of road do not increase, situation walke after enlargement of road lessen jam, vehicle type after enlargement of road increase, and there is there are health trouble after enlargement of road.